Sprawiedliwość a władca w pismach filozoficznych Seneki - Budzanowska, Dominika (Vox Patrum, 2000)
Justice is one of the most important features in the government of the State. The Roman philosopher and politician Seneca wrote much about it. Seneca wanted the sovereigns to be philosophers as it was in the old days, the golden age. Good laws were always created by wise men like Solon or Licurg. It is the love of virtue that forms righteous men and helps them to deal with changing fortune. Pride and terror do not assure the power of the rulers in the future. Many bad sovereigns like Dionysius of the Syracuse, Alexander the Great, Pompey or Caesar, who brought many disasters on people, had themselves experienced the fatal results of power. Somebody’s ill luck will never bring happiness to anyone.